Political Dynamics in Cirebon from the 17th to 19th Century - Suparman, Suparman; Sulasman, Sulasman; Firdaus, Dadan (TAWARIKH, 2017)
ABSTRACT: After being left by Girilaya in 1662, the situation of Cirebon was not condusive. His generation, the Prince of Wangsakerta, was in the difficult situation because he was the prisoner of Trunojoyo in Kediri. Then, he asked for help to Sultan Ageng Tirtayasa of Banten to freed and protect him. Afterward, Sultan Ageng Tirtayasa inaugurated the Princes of Cirebon, namely: Syamsuddin Martawijaya as âSultan Sepuhâ or Old Sultan; Badrudin Kartawijaya as âSultan Anomâ or Young Sultan; and Pangeran Wangsakerta as âPanembahanâ or Prime Minister of Carbon. After being together in Cirebon, there was quarrel though there was no civil war among them. The internal conflict of the Cirebon palace family gave chance to outside, which was VOC (Verenigde Oost-Indische Compagnie or Dutch East India Company) to do intervention. Finally, the VOC bound Sultans of Cirebon by variety of contracts (engagement) under the cloak to make a peace either to get commercial monopoly. Since 1681, the authority of Cirebon Sultans had experienced degeneration as the impact of change had brought Dutch colonialism. Althought, the title of Sultan was still carried, the authority had been disappeared. Every decision considered important things, including the change of Sultan had to get agreement from Governor-General in Batavia or Jakarta now. At 1809, H.W. Daendels organized government reorganization by issuing âReglement van Bestuur voor de Cheribonsche Landenâ that ended the political authority of Cirebon Sultans. KEY WORDS: Political Dynamics; Internal Conflicts; History of Cirebon Sultanates; Reorganization; Dutch Colonialism.Â Â About the Authors: Suparman, Sulasman, and Dadan Firdaus are the Lecturers at the Faculty of Adab and Humanities UIN SGD (State Islamic University, Sunan Gunung Djati) Bandung, Jalan A.H. Nasution No.105, Cipadung, Bandung 40614, West Java, Indonesia. For academic interests, the authors are able to be contacted via e-mail at: suparmanjassin@yahoo.comRecommended Citation: Suparman, Sulasman & Dadan Firdaus. (2017). âPolitical Dynamics in Cirebon from the 17th to 19th Centuryâ in TAWARIKH: International Journal for Historical Studies, Vol.9(1), October, pp.49-58. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980.Article Timeline: Accepted (August 20, 2017); Revised (September 30, 2017); and Published (October 28, 2017).